(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background Spinal anesthesia is the most common anaesthetic technique for cesarean delivery due to its rapid onset, a dense neural block, little risk of local anesthetic toxicity and minimal transfer of drug to the fetus, as well as little risk of failure of block However incidence of hypotension is one of disadvantages of this technique because of sympathetic blockade. Conventionally, crystalloid preloading has been used to prevent spinal anaesthesia induced hypotension, but it has shown varying results. Therefore, focus is on crystalloid coloading for prevention of spinal induced hypotension. Method An observational prospective study was done on 60 parturients undergoing elective cesarean delivery. Patients were randomized into 2 groups who received either crystalloid preloading or coloading. Parameters assessed were, heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, incidence of hypotension and use of mephentermine. Result In this study, there was significant difference in the incidence of hypotension in both the groups, which was more in preload group. Total dose of mephentermine used was also significantly more in preload group. Conclusion We concluded that crystalloid coloading is beneficial to prevent post-spinal hypotension in patients undergoing elective cesarean delivery, as compared to patients receiving preloading fluid.